INOVASI PELAYANAN PERIZINAN MELALUI SSWALFA (SURABAYA SINGLE WINDOW) DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK DI KELURAHAN BALAS KLUMPRIK KECAMATAN WIYUNG KOTA SURABAYA - Anantha, Randy Agung; Eprilianto, Deby Febriyan (Universitas Negeri Surabaya, 2025)
This study examines the implementation of the SSWALFA website as an E-Government innovation for permit services in Balas Klumprik Village, Surabaya City. The website is used across all Regional Government Organizations (OPD) in Surabaya, including Balas Klumprik Village. However, in practice, several challenges still hinder the effectiveness of public services. This research employs a qualitative descriptive method, with data collected through interviews, observations, and documentation. The collected data is analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that SSWALFA provides significant benefits. Based on the relative advantage indicator, the website simplifies the permit application process and document verification. In terms of image, the use of SSWALFA has positively impacted the reputation of Balas Klumprik Village. Regarding compatibility, the innovation aligns well with existing values and has been widely accepted without resistance. The ease of use indicator shows that SSWALFA offers convenient access for the community. Lastly, the use intention indicator highlights an increasing frequency of SSWALFA usage each month. However, the lack of widespread socialization has resulted in many residents being unaware of the website. Therefore, this study recommends expanding public awareness efforts through social media platforms such as Instagram, TikTok, and YouTube to improve community engagement with SSWALFA.